Retinal microvasculature observations of fellow eyes after intra-arterial chemotherapy for unilateral retinoblastoma using optical coherence tomography angiography - Chen, Yijing; Mao, Jianbo; Xiang, Ziyi; Zhang, Zhengxi; Zhang, Shian; Wu, Sulan; Shen, Lijun (Frontiers in Medicine, 2023)
Purpose To investigate the characteristics of the retinal microvasculature of the fellow eyes in patients with unilateral retinoblastoma (RB) after intra-arterial chemotherapy (IAC) through optical coherence tomography angiography. Methods This retrospective study enrolled 11 fellow eyes of patients with unilateral RB receiving IAC (group I), nine fellow eyes of patients with unilateral RB receiving IAC and intravenous chemotherapy (IVC) (group II), and 14 age-matched normal eyes (control group). Optical coherence tomography angiography was performed on all individuals. Vascular density of superficial capillary plexus and deep capillary plexus (DCP), foveal avascular zone related parameters, and retinal thickness were measured and compared among the three groups. Results There was no statistical difference in age and logMAR visual acuity among the three groups. Compared with the control group, the vascular density of the DCP was lower in group I and II. Decreased vascular density of FD-300 and thinner thickness of outer plexus layer to Bruch’s membrane were detected in group II compared with the control group. The vascular density and retinal thickness showed no differences between group I and II. Conclusion The decreased vascular density in the DCP without measurable visual impairment was observed in fellow eyes after IAC or IAC + IVC for unilateral RB. Further studies with a larger sample would be necessary to determine the clinical significance of these findings.